Актуальність розміру втрат сільськогосподарського й лісогосподарського виробництва на сьогодні - Шворак, Анатолій Максимович; Shvorak, Anatolii M. (Східноєвропейський національний університет ім. Лесі Українки, 2017)
У статті запропоновано механізм індексації нормативів утрат сільськогосподарського й лісогосподарського виробництва як передумови вдосконалення економічного механізму регулювання урбанізації продуктивних земель та надходження додаткових платежів до місцевих бюджетів, які будуть спрямовані на покращення та охорону земель. Actuality of losses size of agricultural and forestry production deposit total today. Losses size of agricultural and forestry production that are subject to reimbursement, is stated in order determined by the decree of the Cabinet of Ministers of Ukraine №1279 from 17.11.1997. From the time the decree was adopted more than 18 years have passed. The article proposes the mechanism of indexation of losses norms of agricultural and forestry production as preconditions of improving economic mechanism of regulation of urbanization of productive lands and earnings to additional payments to local budgets, that will be directed to improving and lands protection.
Actuality of Agricultural Loss and Agricultural Production
Keywords: сільськогосподарські угіддя; сільськогосподарське виробництво; рілля; сінокоси; пасовища; agricultural lands; agricultural production; arable land; hayfields; pastures